2016
DOI: 10.1590/1678-4499.261
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids and phenolics biosynthesis increases mango resistance to infection by Ceratocystis fimbriata

Abstract: Mango wilt, caused by Ceratocystis fimbriata, is one of the most important diseases affecting mango yields in Brazil.Information regarding the biochemical mechanisms involved in mango resistance against C. fimbriata is absent in the literature. Thus, the present study determined and quantified alkaloids and phenolics in the stem tissue of mango plants from Palmer (susceptible) and Ubá

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…For instance, inoculation of D. nobile with MF23, a mycorrhizal fungus previously isolated from the roots of D. officinale, significantly increased total alkaloid content (18.3%) by forming peloton to supply nutrients for their hosts (Zhang et al, 2012). Similarly, Ceratocystis fimbriata infection significantly increased alkaloid accumulation in mango (Araujo et al, 2016).…”
Section: Strategies For Enhancing Dendrobium Bioactive Compounds Prodmentioning
confidence: 99%
“…For instance, inoculation of D. nobile with MF23, a mycorrhizal fungus previously isolated from the roots of D. officinale, significantly increased total alkaloid content (18.3%) by forming peloton to supply nutrients for their hosts (Zhang et al, 2012). Similarly, Ceratocystis fimbriata infection significantly increased alkaloid accumulation in mango (Araujo et al, 2016).…”
Section: Strategies For Enhancing Dendrobium Bioactive Compounds Prodmentioning
confidence: 99%
“…Plant phenolics are synthesized by two different metabolic routes, the malonic acid and the shikimic acid pathways, converging into the phenylpropanopid pathway [ 46 , 84 ]. The shikimic acid pathway produces aromatic compounds in plants, such as the amino acids tyrosine, tryptophan and phenylalanine [ 85 ], but also produces gallic acid as an intermediate compound, which is the precursor of hydrolysable tannins, gallotannins and ellagitannins [ 86 , 87 , 88 ].…”
Section: Role Of Genetics On the Distribution And Biosynthesis Of mentioning
confidence: 99%
“…Tea plants are rich in flavonoids and alkaloid, such as catechins and caffeine, which play roles in plant defense (Kuc, 1995). Several reports have indicated that alkaloids and phenolics can enhance plant resistance during pathogen–host interactions (Ahuja et al, 2012; Araujo et al, 2016). Catechins can inhibit the activity of PG and PL in C. gloeosporioides during interactions with avocado fruits and thereby slow the softening of avocado fruits after harvest (Prusky et al, 1988).…”
Section: Introductionmentioning
confidence: 99%